2009
DOI: 10.1016/j.critrevonc.2008.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Renal cell carcinoma: Risk assessment and prognostic factors for newly diagnosed patients

Abstract: Surgical management of renal cell carcinoma is the most effective treatment for patients with localized disease. In patients with advanced renal cell carcinoma, immune modulation-based therapies are typically used to improve cancer specific survival via anti-angiogenic drugs. Similar to most cancers, tumor grade and stage are linked to the tumor’s biologic potential. Integrating these factors with patients’ performance status can help predict their long-term disease-free survival, the likelihood of tumor recur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 66 publications
0
34
0
Order By: Relevance
“…However, so far tumor stage, tumor grade, and patient performance status remain the most useful and clinically available predictors of RCC patients' outcome (reviewed in ref. 3). Up to now, there exist only few data on prognosis-relevant markers of the immune system, among them a high number of blood granulocytes, which correlates with poor prognosis (4).…”
Section: Introductionmentioning
confidence: 99%
“…However, so far tumor stage, tumor grade, and patient performance status remain the most useful and clinically available predictors of RCC patients' outcome (reviewed in ref. 3). Up to now, there exist only few data on prognosis-relevant markers of the immune system, among them a high number of blood granulocytes, which correlates with poor prognosis (4).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a clinical study revealed that QOL could be an independent prognostic factor for metastatic colorectal cancer patients (Efficace et al, 2008). A recent report suggested that renal carcinoma patients' performance status could be used to predict their long-term disease-free survival, the likelihood of tumor recurrence, and the median time to failure following surgery and immunotherapy (Downs et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…1 In addition, as the MiT family translocation RCC, Xp11 translocation RCC and t(6;11) RCC categories have been established. 2 Thus, in recent years, progress has been made in discovering the genes responsible for non-clear RCC and in identifying the signals they mediate.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…In non-clear cell RCC, various genes have been identified from the investigation of hereditary forms. 1 MET and fumarate hydratase are the genes associated with types 1 and 2 papillary RCC, respectively.…”
Section: Conflict Of Interestmentioning
confidence: 99%
See 1 more Smart Citation